THE ECONOMIC DIMENSION OF THE PILGRIMS‟ STORIES IN CHAUCER‟S CANTERBURY TALES - Adel El-Sayed Hassan (European Scientific Journal, ESJ, 2014)
Chaucer‘s medieval England in general and London in particularwitnessed a flourishing economy and a prosperous commerce that helpedimprove medieval English people‘s social life. The growth of towns, theexpansion of trade, the development of industry, the monetization ofmarketplace, the use of the credit system and book-keeping, and thecontrivance of effective methods of paying and recovery of debts allcontributed to this economic prosperity. This paper is a study of the storytellingcontent of selected tales from Chaucer‘s Canterbury Tales in terms ofthe commercial notions and values permeating medieval England. Itdemonstrates that most of the economic terms of the day flow into thepilgrims‘ discourse and shape their stories, thus signaling medieval Englishpeople‘s consciousness of the marketplace tradition. It is within thiseconomic background and commercial framework that many topics ofuniversal interest are addressed.